Immersive virtual reality-based learning as a supplement for biomedical engineering labs: challenges faced and lessons learned - Tandon, Ishita; Maldonado, Vitali; Wilkerson, Megan; Walls, Amanda; Rao, Raj R.; Elsaadany, Mostafa (Frontiers in Medical Technology, 2024)
Introduction Immersive virtual reality (VR) based laboratory demonstrations have been gaining traction in STEM education as they can provide virtual hands-on experience. VR can also facilitate experiential and visual learning and enhanced retention. However, several optimizations of the implementation, in-depth analyses of advantages and trade-offs of the technology, and assessment of receptivity of modern techniques in STEM education are required to ensure better utilization of VR-based labs. Methods In this study, we developed VR-based demonstrations for a biomolecular engineering laboratory and assessed their effectiveness using surveys containing free responses and 5-point Likert scale-based questions. Insta360 Pro2 camera and Meta Quest 2 headsets were used in combination with an in-person lab. A cohort of 53 students watched the experimental demonstration on VR headsets in the lab after a brief lab overview in person and then performed the experiments in the lab. Results Only 28.29% of students reported experiencing some form of discomfort after using the advanced VR equipment as opposed to 63.63% of students from the previous cohort. About 40% of the students reported that VR eliminated or reduced auditory and visual distractions from the environment, the length of the videos was appropriate, and they received enough information to understand the tasks. Discussion The traditional lab method was found to be more suitable for explaining background information and lab concepts while the VR was found to be suitable for demonstrating lab procedures and tasks. Analyzing open-ended questions revealed several factors and recommendations to overcome the potential challenges and pitfalls of integrating VR with traditional modes of learning. This study provides key insights to help optimize the implementation of immersive VR to effectively supplement in-person learning experiences.